A study of power management approach in a grid connected hybrid renewable generation system - Pranita Rathod; Sujit Kumar Bhuyan; Sanjay Kumar Mishra (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Where sun irradiation is not continuous throughout the day, photovoltaic (PV) cells are used to supply solar power to the grid. A suitable power management plan is required to provide a steady power supply to the grid. The hybrid renewable generation system (HRGS) interconnected to the grid is the subject of this study, which provides a revolutionary power management method and control strategy. PV devices, a battery storage unit (BSU) charged by electricity generated from solar energy, and an auxiliary unit make up the HRGS concept (AU). Maximum power point tracking (MPPT) uses an improved perturb and observe (P&O) method to track maximal energy from solar irradiation. The peculiarity of this approach is that it uses a modified MPPT algorithm to handle power management throughout the process, allowing it to manage continuous power delivery to the grid based on load demand. It is capable of working under any load situation. The action of an L-C filter is utilized to decrease the total harmonic distortion (THD). The HRGS scheme's performance appraisals work correctly, achieve maximum productivity, and continually managing the power provided to the grid in a satisfactory way.